(untitled) - Ezgi Dirgar; Betül Tosun; Siyabe Arslan (University of Ostrava, 2021)
Aim: This study was carried out with the aim of evaluating the attitudes of nurses to workplace incivility. Design: A cross-sectional study. Methods: This study was implemented with the participation of 195 nurses working in a hospital in southeastern Turkey. The Nurse Information Form and Nursing Incivility Scale were used as data collection tools. Results: When the total scores for the scale were compared in terms of the working hours of the participants, it was found that those working only night shifts had higher scores than those working only during daytime hours (p = 0.036). A total of 43.6% of the participants thought that their colleagues' attitudes towards them were uncivil. When this situation was evaluated in terms of total scale scores, it was found that participants who felt that they were being treated uncivilly had higher scores (p = 0.030). Conclusion: Nurses were exposed to incivility in the work environment due to stressors such as insufficient number of nurses on wards and the pattern of shifts. Nurses who felt they were being treated uncivilly had higher incivility scale scores.